Investigating the Mediating Role of Organizational Commitment in the Relationship between Leadership, Motivation, Organizational Culture, and Work Discipline - Sukarji, Sukarji (JURNAL AL-TANZIM, 2023)
This research aims to determine and analyze the influence of leadership, motivation, and organizational culture on employee work discipline with organizational commitment as an intervening variable at MAN Tulungagung, East Java, Indonesia. The research method is quantitative with an explanatory research approach with a survey approach. Research data was taken from 79 teachers who were the sample for this research. This research analyzes data using multiple regression analysis. The results of the research show that 1) leadership has a significant effect on organizational commitment; 2) Organizational culture has a significant effect on organizational commitment; 3) Leadership has a significant effect on work discipline; 4) Organizational culture has a significant effect on work discipline; 5) Leadership has an indirect effect on work discipline through organizational commitment, which means there is a mediating influence. So, organizational commitment can mediate between organizational culture and work discipline. Organizational culture has an indirect effect on work discipline through organizational commitment, which means there is no mediating influence. So, organizational commitment cannot be a mediating variable between organizational culture and work discipline.